Development of the citizens measure into a tool to guide clinical practice and its utility for case managers. Issue 3 (3rd July 2017) - Bellamy, Chyrell D.; Kriegel, Liat; Barrenger, Stacey; Klimczak, Michele; Rakfeldt, Jaak; Benson, Victoria; Baker, Michaella; Benedict, Patricia; Williamson, Bridgett; MacIntyre, Gillian
ABSTRACT: A measure of citizenship was developed and validated by Rowe and colleagues (O'Connell, Clayton, & Rowe, 2017 ). The items clustered around the 5 Rs of citizenship as defined by Rowe et al.: relationships, rights, resources, roles, and rights, and a sense of belonging. Although a measure has its utility in clinical settings, to address time constraints and other administrative burdens expressed by providers in their day-to-day practice, a citizens tool was developed as a practical way that providers can enhance dialogue between providers and clients on citizenship for clients served in mental health and criminal justice reentry settings. This article describes the development of the tool, testing of the tool's utility with case managers, and implications for practice.